Studi Bibliometrik Jurnal Media Informatika 2018-2022 - Ronal Watrianthos; Ahmad Habin Sagala; Rahmi Syafriyeti; Yuhefizar Yuhefizar; Mesran Mesran (JURNAL MEDIA INFORMATIKA BUDIDARMA, 2023)
This study aims to conduct a bibliometric analysis of the Budidarma Informatics Media Journal (MIB) for the 2018-2022 period using the Dimensions database. The period produced 683 publications which then became the dataset in this study. The dataset was analyzed using Bibliometrix R-package Biblioshiny, and research trends were mapped using VOSviewer visualization. The analysis results show that the collaboration index of MIB journals has a moderate value and tends to be low, although the annual growth rate of 79.08% looks very significant. The number of citations over five years only amounted to 157, so the average citation per article was 0.22. The average FCR is 0.16, which indicates a citation that is well below average. The results of testing Lotka's postulates for author productivity in this period showed a significant difference between the analysis results and the theory in Lotka's postulates. As for trends, research related to "algorithms" became the most dominant word and the center of the cluster connected to other clusters, becoming the most widely used research topic.